2018
DOI: 10.3892/ol.2018.7865
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Pim-2 induces cell cycle arrest in the G0/G1 phase via the p53-non-dependent p21 signaling pathway

Abstract: Pim-2 is a serine/threonine protein kinase that is highly expressed in various types of cancer, with essential roles in the regulation of signal transduction cascades, which promote cell survival and proliferation. The present study demonstrated that Pim-2 was expressed in cells lines derived from hematopoietic tumors and lung cancer. In vitro, downregulation of Pim-2 by short interfering RNA inhibited proliferation and delayed G0/G1 cell cycle progression in K562 leukemia, RPMI-8226 multiple myeloma, and H129… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…One explanation we considered relies on the differential expression of the cell cycle inhibitor, p21 WAF1/CIP1 , which is dependent on the p53 status of the cells and seems to make HepG2 cells with wt p53 and thus higher p21 WAF1/CIP1 expression more sensitive to PIM2 knockdown than Huh-7 with mutant p53 and a low p21 WAF1/CIP1 expression. This is in line with the findings of Liu et al, who described a p21 WAF1/CIP1 -dependent cell cycle block in G0/G1 upon PIM2 knockdown in the non-small cell lung cancer cell lines A549 and H1299 (34). However, our findings in the Huh-7 cells also suggest an additional, p21 WAF1/CIP1 -independent mechanism of the cell cycle regulation by PIM2 in liver cancer cells, since the ectopic overexpression of wt p21 WAF1/CIP1 in this cell line led to an only slight increase in sensitivity towards PIM2 knockdown.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…One explanation we considered relies on the differential expression of the cell cycle inhibitor, p21 WAF1/CIP1 , which is dependent on the p53 status of the cells and seems to make HepG2 cells with wt p53 and thus higher p21 WAF1/CIP1 expression more sensitive to PIM2 knockdown than Huh-7 with mutant p53 and a low p21 WAF1/CIP1 expression. This is in line with the findings of Liu et al, who described a p21 WAF1/CIP1 -dependent cell cycle block in G0/G1 upon PIM2 knockdown in the non-small cell lung cancer cell lines A549 and H1299 (34). However, our findings in the Huh-7 cells also suggest an additional, p21 WAF1/CIP1 -independent mechanism of the cell cycle regulation by PIM2 in liver cancer cells, since the ectopic overexpression of wt p21 WAF1/CIP1 in this cell line led to an only slight increase in sensitivity towards PIM2 knockdown.…”
Section: Discussionsupporting
confidence: 92%
“…S4A). Recently, Liu et al reported that PIM2 induced cell cycle arrest in the G0/G1 phase via p53-independent, but p21 WAF1/CIP1 -dependent signaling in lung cancer cell lines (34). Thus, in this study, we examined whether the restoration of p21 WAF1/CIP1 expression in the Huh-7 cells would enable a more sensitive cell cycle regulation following PIM2 knockdown.…”
Section: Cell Cycle Block In G0/g1 Phase Upon Pim2 Knockdownmentioning
confidence: 93%
“…Three members of proto-oncogene serine/threonine kinase family have been identified, including pim-1, pim-2 and pim-3 (25,26). It has been reported that pim-1 is involved in regulating cell cycle progression and apoptosis (26); and has been detected to be heavily expressed in numerous cancers including prostate cancer, Burkitt's lymphoma, oral cancer and a variety of hematopoietic lymphomas (27,28). Therefore, to study the role of pim-1 in the prostate cancer physiology, endogenous pim-1 expression was knocked down in androgen-independent prostate cancer cells, including PC3, DU145 and PC3/DDP, using the shRNA approach.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results showed that PFD upregulated p21 levels without requiring functional p53 in PCCs. The several previous studies revealed that p53-independent mechanism for p21 upregulation may contribute to the cell cycle response [33][34][35]. Further studies are required to verify the existence of a p53-independent signaling pathway in this context.…”
Section: Discussionmentioning
confidence: 99%